Dihydroartemisinin Inhibits Laser-Induced Choroidal Neovascularization in a Mouse Model of Neovascular AMD - Li, Xun; Gao, Sheng; Zhang, Yun; Xin, Mei; Zuo, Cheng; Yan, Naihong; Xia, Qingjie; Zhang, Meixia (Frontiers in Pharmacology, 2022)
Purpose: Choroidal neovascularization (CNV) is the main pathogenic process and a leading cause of severe vision loss in neovascular age-related macular degeneration (AMD). We investigated the antiangiogenic efficacy of dihydroartemisinin (DHA) in an experimental laser-induced CNV mouse model. Methods: After fluorescein angiography confirmed that CNV was induced by laser photocoagulation in C57BL/6J mice, DHA or vehicle was given by intragastric administration once a day. On day 6 and day 12, fluorescein angiography, optic coherence tomography, and flat-mounting analysis were performed to grade CNV leakage, measure CNV thickness and evaluate CNV areas, respectively. Immunofluorescence staining and Western blot analysis were performed to evaluate the expression of NF-κB, VEGF, and VEGFR2. To confirm the safety of intragastric DHA application, changes in retinal morphology and neural cell apoptosis were tested by histopathological examination and TUNEL assay. Results: Intragastric administration of DHA significantly suppressed CNV leakage and CNV formation in both thickness and area. Immunofluorescence showed that DHA suppressed VEGFR2 and NF-κB p65 expression in laser-induced lesions. Compared to the normal group, the protein expression of VEGF, VGFER2, NF-κB p65, and NF-κB1 p50 increased significantly in the vehicle group after laser photocoagulation, while it was profoundly inhibited by DHA treatment. In addition, histopathological examination and TUNEL analysis showed no obvious evidence of retinal toxicity caused by DHA. Conclusion: Systemic administration of DHA can effectively inhibit laser-induced CNV formation in mice, which might be due to the suppression of the classic NF-κB signaling pathway and downregulation of VEGFR2 and VEGF expression. The current results suggest that DHA could be a natural potential alternative therapeutic strategy for neovascular AMD.